Patterns of the crematogaster-macaranga association: the ant partner makes the difference - Hashim, Rosli; Feldhaar, H.; Fiala, B.; Maschwitz, U. (2003)
One of the most species-rich ant-plant mutualisms worldwide is the palaeotropical Crematogaster-Macaranga system. Although the biogeography and ecology of both partners have been extensively studied, little is known about the temporal structuring and the dynamics of the association. In this study we compared life-history traits of the specific Crematogaster (Decacrema) partner-ants and followed the development of ant colonies on eight different Macaranga host plant species, from colony founding on saplings to adult trees in a snapshot fashion. We found differences in the onset of alate production, queen number and mode of colony founding in the ant species and examined the consequences of these differences for the mutualism with the host plant. The lifespan of some host plants and their specific ant partners seemed to be well matched whereas on others we found an ontogenetic succession of specific partner ants. The partner ants of saplings or young plants often differed from specific partner ants found on larger trees of the same species. Not all specific Crematogaster species can re-colonize the crown region of adult trees, thus facilitating a change of ant species. Therefore lifespan of the ant colony as well as colony founding behaviour of the different partner ant species are important for these ontogenetic changes. The lifespan of a colony of two species can be prolonged via secondary polygyny. For the first time, also primary polygyny (pleometrosis) is reported from this myrmecophytic system.